1988
DOI: 10.1029/ja093ia06p05959
|View full text |Cite
|
Sign up to set email alerts
|

Role of equatorial ionization anomaly in the initiation of equatorial spread F

Abstract: A comparative study is made of the changes in the latitudinal structure of the F region electron density at fixed altitudes in the Indian equatorial region on days with and without postsunset onset of equatorial spread F, using (N‐h) profile data of Ahmedabad (dip latitude 18.6°N), Waltair (dip latitude 10.6°N), and Kodaikanal (dip latitude 1.5°N). It is found that on spread F days the ratio of the electron density in the altitude region 270 ‐ 300 km between Ahmedabad and Waltair showed a sudden enhancement st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 23 publications
4
75
0
Order By: Relevance
“…Similarly from Fig. 2b There are several studies relating the equatorward TEC gradient with the occurrence of post-sunset scintillations (Raghavarao et al, 1988;Ray et al, 2006). This is perhaps for the first time that efforts are being made to correlate occurrence of post-sunset scintillations with the poleward TEC gradient in the Indian longitude sector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly from Fig. 2b There are several studies relating the equatorward TEC gradient with the occurrence of post-sunset scintillations (Raghavarao et al, 1988;Ray et al, 2006). This is perhaps for the first time that efforts are being made to correlate occurrence of post-sunset scintillations with the poleward TEC gradient in the Indian longitude sector.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of a developed equatorial ionization anomaly (EIA) in the afternoon hours on the subsequent development of equatorial ionization density irregularities during postsunset hours was suggested by Raghavarao et al (1988) and validated by several workers (Valladares et al, 2001(Valladares et al, , 2004Ray et al, 2006;Rama Rao et al, 2006;Ram et al, 2006;Nava et al, 2007). However the majority of the validation exercise was performed at locations existing between the magnetic equator and the northern and southern crests of the EIA.…”
Section: Introductionmentioning
confidence: 99%
“…Maruyamma and Matuura (1984) suggested a mechanism wherein strong meridional winds create a N-S asymmetry in the EIA, thus producing substantial changes in E-region integrated conductivities, which, in turn, control the post-sunset F-region height rise and the triggering of ESF. Raghavarao et al (1988) experimentally showed the intensification of the crest-to-trough ratio of the EIA well in advance of the onset of ESF linking the EIA and the ESF. Following this, Sridharan et al (1994) demonstrated the existence of a precursor in the OI 630 nm day glow that represented the EIA strength which facilitated the prediction of ESF at least 2 h prior to its actual occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…By a careful analysis of ground based ionospheric data, a close linkage between EIA and ESF was shown by Raghavarao et al (1988), Alex et al (1989) and Jayachandran et al (1997). The basic mechanism responsible for the generation of ESF is the Collisional Rayleigh-Taylor (CRT) plasma instability.…”
Section: Introductionmentioning
confidence: 99%
“…It is the background electrodynamic and neutral dynamic conditions that basically dictate the occurrence/non-occurrence of ESF on a particular day. Earlier studies have tried to make an attempt to forecast the occurrence of ESF (Raghavarao et al, 1988;Sridharan et al, 1994;Mendillo et al, 2001;Thampi et al, 2006, and the references therein). These studies imply that the background ionospheric and thermospheric conditions during the daytime play a very crucial role in the generation of ESF.…”
Section: Introductionmentioning
confidence: 99%